Clinical Chemistry and Biochemistry: The Role of Biomarkers and Biomolecules - AHSAN, HASEEB (Universitas Syiah Kuala, 2022)
Biochemistry is a branch of biosciences which deals with the study of chemical reactions that occur in living cells and organisms. It is a subject in which biological phenomenon is analyzed in terms of chemical reactions or metabolic pathways. Biochemistry has been previously named as biological chemistry, chemical biology, clinical chemistry, chemical pathology, physiological chemistry, including medical biochemistry and clinical biochemistry. Medical biochemistry studies the chemical composition and physiological reactions in the human body. Clinical biochemistry is the measurement of chemicals or analytes in body fluids for the diagnosis, monitoring and management of patients with various diseases such as diabetes, cardiovascular diseases, etc. An increase in the number and availability of laboratory diagnostics has helped in the solution of clinical problems. Particularly important is the contribution of clinical chemistry to the diagnosis and monitoring of diabetes. The importance of lipids and lipoproteins for public health has increased with clinical studies showing the benefit of lipid lowering in cardiovascular diseases. An understanding of clinical chemistry and biochemistry would be useful in the study of medical and allied sciences for the advancement of knowledge in academic and professional courses. This review article is an attempt to understand the scope and significance of basic and applied aspects of biochemistry